Perbandingan Pelayanan Jasa Pelabuhan Manual Ke Sistem Syahbandar Online pada PT. Unggul Sejahtera Raya Teluk Bayur - Hadi Nainggolan; Meriah Kita Deliani N (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This paper explains the comparison of manual port service system to the Online Harbor Master system. The method used in this study is field research. The author conducted direct observations and interviews with the company and library research where the author obtained material or paper materials from books in the library or other reading sources related to the topic taken. The Online Harbor Master System is an open and neutral electronic portal to facilitate the exchange of data and information on port services quickly, safely, neutrally and easily which combines with related government agencies, port business entities and logistics industry players to improve better port competitiveness globally. The purpose of this study is to determine the comparison of manual port service to the Online Harbor Master System. The comparison between the manual system and the Online Harbor Master System is that manual work takes a lot of time and money. All activities must be done directly or face to face to the Harbor Master. Factors that influence are the amount of time and costs incurred, for example, applications are still manual, the queue for applications still comes to the Harbor Master or face to face, still uses a lot of paper, and all applications are not in one system. In the service process using the Online Harbor Master System, the effect felt is more efficient and makes it easier for agents to enter data on ships that want to enter the port.